HSP70 in Human Diseases and Disorders (Heat Shock Proteins, 2018)
The book HSP70 in Human Diseases and Disorders provides the most comprehensive review on contemporary knowledge on the role of HSP70 family - one of the most studied HSP - in human diseases and disorders. Using an integrative approach to expand our current understanding of HSP70 functions, the contributors provide a synopsis of novel mechanisms by which HSP70 is involved in the regulation of human diseases and disorders. Key basic and clinical research laboratories from major universities and academic medical hospitals around the world contribute chapters that review present research activity and importantly project the field into the future. The book is a must read for medical students and residents, clinical and basic science researchers, postdoctoral fellows and graduate students in the fields of Medicine, Physiology, Clinical Trials, Biotechnology, Molecular Medicine and Pathology.